Brain Endothelial Erythrophagocytosis and Hemoglobin Transmigration Across Brain Endothelium: Implications for Pathogenesis of Cerebral Microbleeds - Chang, Rudy; Castillo, Juan; Zambon, Alexander C.; Krasieva, Tatiana B.; Fisher, Mark J.; Sumbria, Rachita K. (Frontiers in Cellular Neuroscience, 2018)
Peripheral endothelial cells are capable of erythrophagocytosis, but data on brain endothelial erythrophagocytosis are limited. We studied the relationship between brain endothelial erythrophagocytosis and cerebral microhemorrhage, the pathological substrate of MRI-demonstrable cerebral microbleeds. To demonstrate the erythrophagocytic capability of the brain endothelium, we studied the interactions between brain endothelial cells and red blood cells exposed to oxidative stress in vitro, and developed a new in vitro cerebral microbleeds model to study the subsequent passage of hemoglobin across the brain endothelial monolayer. Using multiple approaches, our results show marked brain endothelial erythrophagocytosis of red blood cells exposed to oxidative stress compared with control red blood cells in vitro. This brain endothelial erythrophagocytosis was accompanied by passage of hemoglobin across the brain endothelial monolayer with unaltered monolayer integrity. In vivo and confocal fluorescence microscopy studies confirmed the extravasation of RBC exposed to oxidative stress across brain endothelium. These findings, demonstrating erythrophagocytosis mediated by the brain endothelial monolayer and the subsequent passage of iron-rich hemoglobin in vitro and RBC in vivo, may have implications for elucidating mechanisms involved in the development of cerebral microbleeds that are not dependent on disruption of the microvasculature.